2015
DOI: 10.7314/apjcp.2015.16.8.3121
|View full text |Cite
|
Sign up to set email alerts
|

Association of Educational Levels with Survival in Indian Patients with Cancer of the Uterine Cervix

Abstract: The main objective of this paper was to assess the influence of educational level on the survival of uterine cervix cancer patients in our population. A total of 224 patients were registered in our registry, of which 178 had information on stage and different educational levels. The overall median survival (MS) was 23 months, with values of 18.5, 20.7 and 41.3 months for the illiterate, literate and qualified groups, respectively. In the illiterate patients, stage I was seen in 2.6% and stage IV in 11.8%, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Risk factors significantly affect prognosis (8,17). In the study results, education is one of the risk factors that influence the survival rate, so it can be concluded that education can affect the prognosis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Risk factors significantly affect prognosis (8,17). In the study results, education is one of the risk factors that influence the survival rate, so it can be concluded that education can affect the prognosis.…”
Section: Discussionmentioning
confidence: 89%
“…In the study results, education is one of the risk factors that influence the survival rate, so it can be concluded that education can affect the prognosis. In the other studies, namely, the level of education related to behavior, health, or the ease of receiving knowledge and resources has a direct and indirect impact on the survival of cervical cancer patients (17).…”
Section: Discussionmentioning
confidence: 99%
“…Tongue cancer is the most common malignant tumor of oral cancer. The incidence of tongue cancer has increased in the past 30 years [1,2]. Surgical resection is an essential strategy for the treatment of tongue cancer.…”
Section: Introductionmentioning
confidence: 99%